The Influence Of Overtime And Incentives On Employee Performance At PT. Asam Jawa Medan - Situmorang, Tiurimaida; Sahputra, Ngatno; Firah, Al (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
The purpose of this study was to determine the effect of Overtime and Incentives on Employee Performance at PT Asam Jawa Medan. 47 respondents with saturated sampling technique using primary data and secondary data. The data analysis technique used is multiple linear regression. The results obtained overtime has a positive and significant effect on employee performance with a value of t (count)> t(table) (2.225> 2.015) with Sig 0.031 <0.05 H 0is rejected so that the better the overtime set by the company, the employee performance will increase. There is a significant effect of incentives on employee performance with a value of t (count)> t(table) (2.277> 2.015) with Sig 0.021 <0.05 H 0is rejected so that the higher the incentives provided by the company, the employee performance will increase. There is a simultaneous influence of overtime and incentives on employee performance with a value of F (count)> F(table) (6.557>3.20) with Sig. 0.003 <0.05 H 0is rejected. From the results of the R test obtained 0.778, it means that the influence of overtime and incentives is 0.778, the R-Square value is 0.605 (60.5%) the remaining 39.5% employee performance is influenced by other variables. Based on the results of the analysis, it shows that Overtime and Incentives both simultaneously and partially have a positive and significant effect on Employee Performance at PT Asam Jawa Medan.